2013
DOI: 10.1186/1471-2407-13-226
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender and age on the survival of patients with nasopharyngeal carcinoma

Abstract: BackgroundThe prognostic value of gender and age in the survival of nasopharyngeal carcinoma (NPC) patients treated with intensity-modulated radiotherapy (IMRT) is unclear. Several studies have suggested a female advantage in the prognosis of solid tumors. We investigated the relationship between gender differences and disease outcome in NPC patients treated with IMRT in South China.MethodsA total of 299 patients with non-disseminated NPC were analyzed retrospectively. IMRT was delivered with a simultaneous mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
56
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 17 publications
10
56
1
2
Order By: Relevance
“…Our finding was highly consistent with prior reports in [7,8] and out of [16,17] clinical trials. However, age showed no association with survival in another two trials that focused on the effect of concurrent chemotherapy [10] and adjuvant chemotherapy [9] respectively.…”
Section: Discussionsupporting
confidence: 83%
“…Our finding was highly consistent with prior reports in [7,8] and out of [16,17] clinical trials. However, age showed no association with survival in another two trials that focused on the effect of concurrent chemotherapy [10] and adjuvant chemotherapy [9] respectively.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies were reported about age as a prognostic factor in NPC [32][33][34][35][36]. Many of these indicated that younger age was related with favourable outcomes, but others reported that the disease course in younger patients was poorer than that in old patients [36,37].…”
Section: Discussionmentioning
confidence: 97%
“…Also the patients with intracranial extension had low overall survival which is turn depicts the advanced stage of disease. The prognostic role of age and gender on the survival of NPC was seen in the study of Xiao et al [22] where in younger men were more likely to have distant metastases and exhibited inferior overall survival and disease progression-free survival rates.…”
Section: Discussionmentioning
confidence: 97%